Successful rituximab treatment for severe rapidly progressive interstitial lung disease with anti-MDA5 antibody-positive juvenile dermatomyositis: a case report and literature review - Kentaro Nishi; Masao Ogura; Naotaka Tamai; Naofumi Gima; Kentaro Ide; Goro Koinuma; Koichi Kamei; Shuichi Ito (BMC, 2022)
Abstract Background Rapidly progressive (RP) interstitial lung disease (ILD) is a life-threatening complication of juvenile dermatomyositis (JDM); however, it is generally refractory to treatment; to the best of our knowledge, no evidence-based treatment has been established for RP-ILD yet. We present the case of a 2-year-old girl with RP-ILD who showed resistance to treatment with methylprednisolone, cyclosporine A, cyclophosphamide, immunoglobulin, and plasma exchange (PE) and was finally treated with extracorporeal membrane oxygenation. We further present a literature review of 18 cases of JDM with RP-ILD. Case presentation A 2-year-old girl presented with malar rash, mild muscle weakness, and weight loss for a few months before admission. She had a history of dry cough and dyspnea for a few days, followed by rapid respiratory failure. The patient was diagnosed with JDM with RP-ILD through physical examination (malar rashes and Gottron's sign) and based on the finding of myositis on femoral magnetic resonance imaging, elevated levels of serum muscle enzymes, positive anti-melanoma differentiation-association gene 5 (MDA5) antibody (> 7,500 index), elevated level of Krebs von den Lungen-6 glycoprotein (KL-6; 3,420 U/mL), and extensive ground-glass opacities with consolidation in the bilateral lungs on chest high-resolution computed tomography. She received combination therapy, including methylprednisolone pulse therapy, followed by oral prednisolone and intravenous cyclosporine A, cyclophosphamide, and immunoglobulin. On day 11 of hospitalization, she was placed on ventilation support and PE was initiated. However, her respiratory condition continued to deteriorate and veno-venous extracorporeal membrane oxygenation was started on day 24 of hospitalization. Rituximab was administered on day 28. After 2 weeks of rituximab therapy initiation, her respiratory condition showed gradual improvements. Eventually, on day 52 of hospitalization, the patient could be weaned off extracorporeal membrane oxygenation. Finally, she was discharged with minimal ventilation support and no neurological complications 11 months after admission. Conclusions Our literature review suggest that JDM with RP-ILD has a high mortality rate. In JDM, rituximab may be a promising treatment option for RP-ILD. In the future, the efficacy of rituximab in the early phases of ILD should be investigated.